International production, international finance, and development: a study of integration into global value chains - Sinha, Bhavya, author; Vasudevan, Ramaa, advisor; Braunstein, Elissa, committee member; Miller, Ray, committee member; Stevis, Dimitris, committee member (Colorado State University. Libraries, 2025)
This dissertation studies the exploitation of labor and accumulation of capital in developing and developed countries with their integration into global value chains (GVCs). The three chapters analyze the distribution of income between labor and capital in manufacturing GVCs, the integration of countries through GVC participation and international finance, and the competitiveness from squeezing labor in export-oriented manufacturing firms in India. Chapter 1 examines the association between declining labor shares and rising participation rates in manufacturing GVCs for developing and developed countries. It finds that a rise in a country's participation rate index in manufacturing GVCs is associated with a decline in its labor share for manufacturing workers in both developing countries and developed countries. Chapter 2 investigates the co-integration of the globalization of production in GVCs and financialization in private capital. It finds significant evidence of co-integration between increased participation in GVCs and increased integration with financial capital for developing and developed countries. Further, an increase in international financial integration is associated with an increase in backward linkages for developing countries and an increase in forward linkages for developed countries, thus providing evidence of the double subordination of developing countries in networks of global production and global finance. Chapter 3 explores the export competitiveness of Indian manufacturing firms and their association with labor shares and labor productivity. It finds manufacturing firms, especially in export-oriented enclaves, expand their competitiveness in export markets by suppressing labor shares and boosting labor productivity.
Keywords: financial subordination; labor share; global value chains; export-oriented production